COMPILATION METHOD AND EXPERIMENTAL STUDY OF GRINDING MACHINE SPINDLE LOAD SPECTRUM - CHI YuLun; LI HaoLin (Jixie qiangdu)
With high precision grinding technology development,the requirement for machine tool reliability is higher and higher.The load spectrum of grinding is key scientific basis of building the grinding machine spindle reliability experiment platform.Based on bearing ring machine tool grinding process,the load spectrum signal characteristic and processing method is studied through long time grinding spindle load measurement,recoding and analysis.Then,the compilation method is provided to get load spectrum.At last,the programmed load spectrum for "idle-grinding-idle"is drawn,which is consistent with real field load.It provide the loading condition and theory basis for grinding machine tool spindle reliability experiment,and also is very important to improve machine tool spindle design.